Shortcomings in Traffic Control Devices on Rural Highways of Pakistan and their Rectifications - Tayyab, Saad; Haq, Fazal; Khurshid, Muhammad Bilal (Review of Information Engineering and Applications, 2019)
Traffic signs, signals and road markings installed on the roads and highways need a lot of improvements in Pakistan. They do not fulfill the fundamental conditions as per international standards i.e. peculiar shapes, sizes and colors. Among all the reasons the most important being the lack of a proper Manual, outlining the warrants and other details essential for putting up proper signs. The problem is further being made worse by the lack of qualified traffic engineers, not fully familiar with the art and science of traffic signs. As a result, the field engineers and contractors were left to their own wishes with regard to design and installing of the road signs. Where as in developed countries there are many signs manufacturing firms who are specialized in this particular field. Many international organizations making efforts for the uniformity of markings and road signs in order to improve the safety of roads and to enhance international roads traffic, but in Pakistan not much significant work has been done and is still very much lagging in this industry. This study is aimed to investigate about the improvements that need to be done in traffic signs and markings, there installation and their maintenance. This will help to make the traffic flow more safe and efficient. The up short of all this study is to enhance the best possible safety of the road users by awaking and changing the aptitude and attitude of users towards the traffic control devices.